Symposium on Interactive 3D Graphics and Games 2011
DOI: 10.1145/1944745.1944752
|View full text |Cite
|
Sign up to set email alerts
|

Real-time volumetric shadows using 1D min-max mipmaps

Abstract: To compute single scattering in scenes with occluders (left) we compute a depth image from the camera, and a shadow map from the light. After epipolar rectification, each row of the shadow map is a 1D heightfield. We optimize the computation of the scattering integral by using an efficient data structure (a 1D min-max mipmap, center) over this heightfield. This data structure helps compute the scattering integral for all camera rays in parallel. Our method can render complex high-quality scenes with textured l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…To quickly identify these positions in parallel on the GPU, an epipolar rectification of a shadow map is performed so that light rays are orthogonally aligned with the viewing rays. In later work [Chen et al 2011], speed is further improved using a min-max structure of the depth image from the camera for finding the lit segments of each viewing ray. Whereas they only model homogeneous translucent material, we allow for freely varying material opacities.…”
Section: Related Workmentioning
confidence: 99%
“…To quickly identify these positions in parallel on the GPU, an epipolar rectification of a shadow map is performed so that light rays are orthogonally aligned with the viewing rays. In later work [Chen et al 2011], speed is further improved using a min-max structure of the depth image from the camera for finding the lit segments of each viewing ray. Whereas they only model homogeneous translucent material, we allow for freely varying material opacities.…”
Section: Related Workmentioning
confidence: 99%
“…Equations 2 and 4 integrate quite smooth functions, allowing coarse SVD approximation [Chen et al 2011] to replace the integral by the sum of a few terms. We use a somewhat cruder approximation suggested by Dobashi et al [2002]:…”
Section: Light Transport In Mediamentioning
confidence: 99%
“…Engelhardt and Dachsbacher [2010] sample and interpolate along epipolar planes, where volumetric shadows only change at depth discontinuities. Chen et al [2011] use min-max mipmaps to non-uniformly step along view rays and approximate the airlight integral with a coarse sum.…”
Section: Shadows In Homogeneous Participating Mediamentioning
confidence: 99%
“…While very reasonable in the context of real-time renders, it was our finding that this method introduces too much blur for the quality targets of cinematic offline renders. It has been shown that it is possible to even get away with only a one-dimensional min-max mipmap [Baran et al 2010;Chen et al 2011]. This approach not only rectifies lines to the light, but also camera rays to gain even more performance.…”
Section: Volumetric Renderingmentioning
confidence: 99%